Cerebellar dysfunction in a family harboring the PSEN1 mutation co-segregating with a cathepsin D variant p.A58V - Ehling R; Nosková, Lenka; Stránecký, Viktor; Hartmannová, Hana; Přistoupilová, Anna; Hodaňová, Kateřina; Benke T; Kovacs GG; Strobel T; Niedermuller U; Wagner M; Nachbauer W; et al. (Journal of the neurological sciences, 2013)
Presenile dementia may be caused by a variety of different genetic conditions such as familial Alzheimer's disease, prion disease as well as several hereditary metabolic disorders including adult onset neuronal ceroid lipofuscinosis. We report a multigenerational family with autosomal dominant presenile dementia harboring a cerebellar phenotype. Longitudinal clinical work-up in affected family members revealed ataxia accompanied by progressive cognitive decline, rapid loss of global cognition, memory, visuospatial and frontal-executive functions accompanied by progressive motor deterioration and early death. Linkage analysis and exome sequencing identified the p.S170F mutation of Presenilin 1 in all affected individuals, which is known to be associated with very early onset Alzheimer's disease. Additional search for potentially modifying variants revealed in all affected individuals of the third generation a paternally inherited variant p.A58V (rs17571) of Cathepsin D which is considered an independent risk factor for Alzheimer's disease. Involvement of cerebellar and brainstem structures leading to functional decortication in addition to rapid progressive presenile dementia in this PSEN1 family may therefore indicate an epistatic effect of the p.A58V Cathepsin D variant on the deleterious course of this disease.<ovid:br/><ovid:br/> Copyright © 2013 Elsevier B.V. All rights reserved.
Keywords: mutace; dospělí; nemoci mozečku; presenilin-1; Female; Pedigree; Adult; ženské pohlaví; rodokmen; lidé; Mutation; Genetic Variation; Cerebellar Diseases; Male; Cathepsin D; Alzheimer Disease; kathepsin D; Alzheimerova nemoc; mužské pohlaví; genetická variace; Presenilin-1; Humans